The Effect Of Leverage, Audit Quality, And Earnings Management On The Integrity Of Financial Statements - Safitri, Aidila Safitri; Syaiful Bahri (International Journal of Educational Research & Social Sciences, 2021)
The research has the objective to find out the existence of the leverage, audit quality, and earnings management on the integrity of financial statements. The research population of sub-bank companies listed on the Indonesia Stock Exchange for the period 2019 and 2020 were selected using a purposive sampling technique. The research sample is 31 companies. The types of research data are quantitative data and secondary data sources. The data analysis technique used descriptive statistical analysis, logistic regression analysis and t test. The results of the study of leverage, audit quality, and earnings management have no effect on the integrity of financial statements.